Kazakhstan in World War II : Mobilization and Ethnicity in the Soviet Empire - Carmack, Roberto J. (Book collections on Project MUSE., 2019)
"Just three days after the Wehrmacht launched Operation Barbarossa, the Central Committee of the Kazakh Communist Party convened its fifth plenary session in the Central Asian city of Almaty. Declaring a state of emergency in response to this "treacherous attack by German fascism," the plenum called on the local population to support the Soviet war effort. From 1941 to 1945, hundreds of thousands of Kazakh soldiers would fight under the Soviet banner on the distant battlefields. In Kazakhstan, millions of Kazakh herders, collective farmers, and factory workers would toil under Stalin's militarized labor regime. In the desolate Kazakh countryside, legions of evacuees and deportees would work, starve, and establish new relationships with the local population. The war was, in other words, a seismic event in Central Asian history. Robert Carmack explores how the conflict altered power relations, discourses of identity, and administrative practices in Kazakhstan and the Soviet Union, arguing that World War II accelerated Kazakhstan's integration into the Soviet empire, but in ways that deepened ethnic and social inequalities."--Provided by publisher.